Distribusi Afeksi sebagai Bentuk Aktivasi Hak Suara dalam Ruang Digital Learning - Dalatina Peloggia Gustianingsih (Jurnal Riset Jurnalistik dan Media Digital, 2023)
Abstract.The phenomenon of Covid-19 in Indonesia raises the pros and cons of digital learning which is increasingly widespread. These include a comparison of offline and online learning in elementary and secondary school, the readiness of resources and technology infrastructure, to the question of how the affection distribution process in digital learning works. The purpose of this study was to compare the distribution of affection in online or digital learning in dance extracurriculars in non-formal (community-based) and formal schools. The practice of both is a turning point in the process of critical awareness and understanding which shows that the distribution of affection is and can continue to roll in digital learning. Based on data in the form of experience as a facilitator in non-formal and formal online extracurricular activities, the research method used in this study is Participation Action Research (PAR). The results of the research that has been carried out are: (1) spontaneous and active negotiation also activation of voice rights on all matters related to the learning process, through one of the digital conference platforms; (2) critical understanding that the issue of education is no longer limited to the problem of model/methods used; (3) awareness of learning standards or achievements, by reading and interpreting them not only vertically. Abstrak. Fenomena Covid-19 di Indonesia memunculkan pro dan kontra atas digital learning yang semakin marak. Di antaranya: perbandingan pembelajaran luring dan daring pada sekolah dasar dan menengah, kesiapan sumber daya dan infrastruktur teknologi, hingga pertanyaan mengenai bagaimana proses distribusi afeksi dalam digital learning berjalan. Tujuan penelitian ini adalah memperbandingkan distribusi afeksi dalam pembelajaran daring atau digital learning ekskul tari di sekolah nonformal (berbasis komunitas) dan formal. Praktik keduanya menjadi titik balik proses penyadaran dan pemahaman kritis yang menunjukkan bahwa distribusi afeksi masih dan bisa terus bergulir dalam digital learning. Berdasar data yang berupa pengalaman menjadi fasilitator dalam ekskul daring sekolah nonformal (berbasis komunitas) dan formal, maka metode penelitian yang digunakan dalam penelitian ini adalah participation action research (PAR). Hasil dari riset yang telah dilakukan adalah: (1) adanya negosiasi dan aktivasi hak suara secara spontan dan aktif atas segala hal yang berkaitan dengan proses pembelajaran, melalui salah satu platform digital conference; (2) pemahaman kritis bahwa isu pendidikan tidak lagi sebatas persoalan model/metode yang digunakan; dan (3) penyadaran akan standar atau capaian pembelajaran, dengan cara membaca dan menafsirkannya tidak hanya secara vertikal.